Defense and the Dollar/Economic Controls and Defense (Book). - Cannon, Arthur M.; Simpson, Floyd R. (The Accounting Review, 1954)
Reviews two books on economics. "Defense and the Dollar," by Albert G. Hart; "Economic Controls and Defense," by Donald H. Wallace.